Impact of climate change on trade in Africa - Mamboundou, Pierre; Traoré, Fousseini; Zaki, Chahir (International Food Policy Research Institute, 2024)
The literature on the complex relationship between trade and climate change is rich. While trade can affect climate change through dirty production techniques or carbon emissions due to transport (Brenton and Chemutai 2021), climate change can affect trade through its effect on agricultural productivity (Ben Zaied and Cheikh 2015; Chandio et al. 2020), production, and thus countries’ specialization (Gouel and Laborde 2021), primarily due to high temperatures and water stress (Hamududu and Ngoma 2020). As Africa is a net importer of agricultural products, the consequence is that climate change will likely affect food security in the medium and long term. Against this background, the objective of this chapter is twofold. First, we examine the extent to which African countries are exposed to climate change relative to other regions of the world. Second, we show how Africa’s comparative advantages can be altered with rising temperatures and water stress. Our main findings show that climate change effects in Africa are more pronounced than in other regions, reflected in the increase in extreme weather events associated with rising temperatures and greater variability in precipitation. These developments are likely to increase the number of food insecure people. Furthermore, we identify how climate change can affect African countries’ specialization based on products’ sensitivity to changes in temperature and their dependence on water. We show that several crops (such as leguminous vegetables, edible nuts and coconuts, groundnuts, oilseeds, and oleaginous fruits) will be affected by climate change. Other crops’ production may be less affected, but their future expansion may be limited by climate change–related factors.